Do skill based conditioning games offer a specific training stimulus for junior elite volleyball players? - Gabbett, T. J. (The Journal of Strength and Conditioning Research, 2008)
This study investigated the specificity of skill-based conditioning games and compared the effectiveness of skill-based conditioning games and instructional training for improving physical fitness and skill in junior elite volleyball players. Twenty-five junior volleyball players (mean age ± SE, 15.6 ± 0.1 years) participated in this study. Heart rate data were collected on all players during the Australian Junior Volleyball Championships. After the competition, players were randomly allocated into a skill-based conditioning games group (n = 12) or an instructional training group (n = 13). Each player participated in a 12-week training program that included 3 organized court training sessions per week. No significant differences (P > 0.05) were detected between competition and skill-based conditioning games for the percentage of time spent in low-intensity, moderate-intensity, and high-intensity activities. Skill-based conditioning games induced improvements in vertical jump, spike jump, speed, agility, upper-body muscular power, and estimated maximal aerobic power, whereas technical instruction improved only spike jump and speed. Conversely, instructional training induced meaningful improvements in all measurements of skill, whereas improvements in technical skill after skill-based conditioning games were uncommon and typically small. The results of this study show that skill-based conditioning games offer a specific training stimulus to simulate the physiological demands of competition in junior elite volleyball players. Although the improvements in physical fitness after training were greater with skill-based conditioning games, instructional training resulted in greater improvements in technical skill in these athletes. These findings suggest that a combination of instructional training and skill-based conditioning games is likely to confer the greatest improvements in fitness and skill in junior elite volleyball players.